2018
DOI: 10.1590/1413-785220182604194374
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Program for Elderly and Economy for the Health System

Abstract: Objective:To evaluate the impact of physical activity on the use of the health system and the quality of life in sedentary elderly.Methods:A prospective interventional study was carried out between March 2010 and February 2011 with 100 subjects (60-90 years of age,) divided into active group (AG) and control group (CG). During this period, AG performed physical exercise twice a week in 60-minute sessions and the CG remained sedentary with observation of their activities. Before and after the study, all subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…These findings are in line with those of previous studies. Daher et al found that older adults who did physical activity had a better quality of life and made less use of hospital and emergency services [ 51 ]. Cantarero et al found that visits to the doctor and hospital admissions were lower in those engaging in physical activity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with those of previous studies. Daher et al found that older adults who did physical activity had a better quality of life and made less use of hospital and emergency services [ 51 ]. Cantarero et al found that visits to the doctor and hospital admissions were lower in those engaging in physical activity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, persons engaging in regular exercise also showed lower probability for ED visits, hospitalizations, and deaths. In a previous study, when supervised physical exercise was applied to sedentary older individuals, reductions in ED visits, ED hospitalizations, and length of hospital stays were observed [ 62 ]. A comprehensive approach to reduce modifiable risk factors (e.g., smoking cessation, avoidance heavy alcohol consumption, and engagement in regular exercise) identified in this study would be worthy when considering the burdens on both primary and emergent care.…”
Section: Discussionmentioning
confidence: 99%
“…O exercício físico é capaz de promover a saúde e melhorar a qualidade de vida dos idosos, além de reduzir a utilização de serviços de saúde [10]. E uma alimentação balanceada em macro e micronutrientes com a finalidade de evitar desequilíbrios nutricionais na terceira idade, demonstra ter, também, capacidade de melhorar a qualidade de vida e longevidade [11].…”
Section: […] Para Que Tenhamos Uma Saúde Boa Nós Somos Responsáveis Pelas Nossas Escolhas Nas Práticas Saudáveis Do Nosso Dia a Dia Requeunclassified